Pre-service secondary teachers’ knowledge of the function concept: A cluster analysis approach - José María Marbán; Edgar John Sintema (Department of Mathematics Education, Universitas Muhammadiyah Surakarta, 2020)
Teacher training is a key aspect for the success of any educational system and it is a prior challenge to facein-depth in Zambia. This study explores some dimensions of prospective secondary mathematics teachers’ subject-matter knowledge and pedagogical content knowledge restricted to the topic of the function concept. Data were collected by means of a questionnaire that was administered to a sample of 150 prospective teachers enrolled attwo public universities inCopperbelt, Zambia. A two-step cluster analysis was used to reveal natural grouping within the datasetobtained. As a result, a two-cluster solution was revealedas the solution that best profiled the data, with participants within both clusters scoringlow in the knowledge domains under consideration. To further understand the results a one-way between-subjects multivariate analysis of variance (MANOVA) and a follow-up discriminant function analysis (DFA) were also conducted. Common content knowledge was shown to be the most important factor in discriminating between prospective teachers in Cluster 1 and those in Cluster 2. The knowledge inadequacies identified are certainly worrisome and are likely to be transferred to young learners at secondary schools. Consequently, it is necessary to address with some urgency certain reforms in educational policies for teacher training programs in Zambia.